The Influence of Political Literacy on Student Participation In Democratic Activities on Campus - Muliono; Ibnu Anshori; Muhammad Arifin; Lie Epifani Rachmat Gunadi; Alfi Mufida Rahmawati (Universitas Kristen Cipta Wacana, 2026)
This research aims to analyze the influence of political literacy on student participation in democratic activities on campus and its synchronization with Political Science studies and the Citizenship Education Programme.The research employs a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation of students involved in student organizations and campus democratic activities. The research results indicate that political literacy has a significant influence on the level of student participation in activities campus democracy such as student organisation elections, public discussions, forums for students, and advocacy activities. Students with a good political understanding tend to be more active, critical, and responsible in exercising their rights and democratic obligations. Synchronisation between Political Science studies and Education Citizenship visible on the formation of democratic character, awareness constitutionalism, as well as strengthening participatory values in the academic environment. This research concludes that political literacy is one of the important factors in building a healthy democratic culture in higher education.